Real-life experience with compassionate use of cefiderocol for difficult-to-treat resistant Pseudomonas aeruginosa (DTR-P) infections. Issue 4 (11th December 2021) - Meschiari, Marianna; Volpi, Sara; Faltoni, Matteo; Dolci, Giovanni; Orlando, Gabriella; Franceschini, Erica; Menozzi, Marianna; Sarti, Mario; Del Fabro, Giovanni; Fumarola, Benedetta; Guarneri, Francesco; Lanza, Paola; et al.
Abstract: Objectives: To describe our real-life experience with cefiderocol in XDR and difficult-to-treat resistant Pseudomonas aeruginosa (DTR-P) infections without any other available treatment options. Methods: We included patients with a proven infection due to an XDR/DTR-P, who had failed on previous regimens, and were treated with cefiderocol, following them prospectively to day 90 or until hospital discharge or death. Results: Seventeen patients treated for >72 h with cefiderocol were included: 14 receiving combination regimens (82.4%) and 3 receiving monotherapy (17.6%). Fourteen patients were males (82%) with a median age of 64 years (IQR 58–73). Fifteen patients (88.2%) were admitted to the ICU and five had septic shock (29%). Seven cases (41.2%) were ventilator-associated pneumonia, of which 71% (5/7) occurred in COVID-19 patients. Four were complicated intrabdominal infections, one ecthyma gangrenosum, one nosocomial pneumonia and one empyema, one osteomyelitis, one primary bacteraemia, and one nosocomial external ventricular drainage meningitis. Clinical cure and microbiological cure rates were 70.6% and 76.5%, respectively. There were six deaths (35.3%) after a median of 8 days (IQR 3–10) from the end of treatment, but only two of them (11.7%) were associated with P. aeruginosa infection progression. Conclusions: Our experience collecting this large case series of DTR-P treated with cefiderocol may help clinicians consider this new option in this hard-to-manage setting. Our results are even more relevant in the current scenario of ceftolozane/tazobactam shortage. Importantly, this is the first study providing real-life data indicating adequate cefiderocol concentrations in CSF.